Pelatihan Deteksi Dini Stunting pada Kader - Julhana; Indra Rahmad; Fadlurahmi; Lalu Arwan Darmajaya (CV. CENDIKIA JENIUS INDONESIA, 2026)
Stunting remains a critical public health challenge in Indonesia, necessitating strengthening community-level detection capacity. This study aimed to improve the knowledge and skills of Posyandu (Integrated Service Post) cadres in early stunting detection. The community service program involved 30 Posyandu cadres in Jatibaru Village, Asakota District, Bima City. The intervention used a multi-method approach consisting of interactive lectures, educational booklets, animated video presentations, simulation exercises, and hands-on anthropometric practice. Evaluation used pre- and post-test questionnaires to assess knowledge gains and an observation checklist based on WHO standards to evaluate anthropometric competency. Data were analyzed using a paired t-test. Results showed a significant increase in the mean knowledge score from 58.3 to 87.5 (p < 0.001), with cadres achieving good knowledge increasing from 13.3% to 90.0%. Anthropometric competency levels reached 96.7% for digital scale use, 93.3% for mid-upper arm circumference measurement, 86.7% for length measurement using a measuring board, and 83.3% for growth chart interpretation. This training program effectively improved the cadres' cognitive and psychomotor competencies, supporting community-based stunting prevention and early detection efforts.